Implementation of the Independent Learning Curriculum to Improve the Executive Function of Early Childhood at PAUD Institutions - Luci Irawati; Sudiaryati Sudarto; Siti Rahmawati; Saanih; Rusliah; Armeta Niasari; Lilis Retnowati; Debie Susanti (Universitas Panca Sakti Bekasi, 2024)
The implementation of the the Independent Learning Curriculum in Early Childhood Institutions in Mega Mendung District faces disparities, as many teachers lack comprehension of the Independent Learning Curriculum due to limited references and inadequate training. Moreover, a significant number of teachers struggle with fostering executive functions in early childhood that crucial for children's preparedness as they transition from preschool to higher education levels. To address this issue, Community Service Initiatives (PKM) were conducted in Mega Mendung District, focusing on enhancing the knowledge and skills of Early Childhood teachers in planning, implementing, and evaluating the Independent Learning Curriculum Learning. The one-day workshop employs lecture methods and interactive discussions to improve teachers' understanding, aiming to create a more enjoyable teaching and learning experience through the the Independent Learning Curriculum. This initiative seeks to better equip early childhood teachers and prepare young learners for the challenges of higher-level education.